Wonder Woman/Conan - Simone, Gail (DC Comics, 2018)
"She is Diana of Themyscira, warrior princess of the Amazons. He is Conan the Cimmerian, barbarian scourge of a dozen civilizations. Alone, each is unstoppable. But what happens when these two heroes meet face to face? Dark and malicious magic has driven Wonder Woman and Conan together, stripping Diana of her memories and chaining her destiny to this dark-haired and dangerous stranger. Slavers and gladiators, pirates and predators, an army of witches poised to conquer the world on wings of wickedness: these are the foes the Amazon and the Cimmerian must join together to defeat if they are to restore her rightful name, regain their freedom and save their lands from darkness. But for these mighty warriors, passion runs hot and deep. Will a search for love and a lust for vengeance guide them to their final reckoning with the evil out to destroy them, or tear them apart before they can crush their enemies once and for all?"--